Digitalisasi Sastra Bubiti Melalui Pengembangan E-Modul Berbasis TPACK di Sekolah Dasar: Digitizing Bubiti Literature Through the Development of TPACK-Based E-Modules in Elementary Schools - Miftahul Jannah; Muhammad Fuad; Sumarti Sumarti; Farida Ariyani (ITScience (Information Technology and Science), 2026)
Bubiti oral literature, poetry from the Lampung Pubian tradition that is starting to become extinct due to limited documentation, is rarely used by the Lampung community, and there is a lack of digital teaching materials. Other Lampung literary research only focuses on social functions or other general types of literature; this study specifically digitizes Bubiti literary texts that have never been documented in learning media before. This study aims to develop and test the feasibility and effectiveness of Bubiti text e-modules based on Technological Pedagogical Content Knowledge (TPACK) for elementary school students. This study uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method development design. The feasibility test was carried out through expert validation, while the effectiveness test used a one-group pretest-posttest design for 27 fourth-grade students. Data were analyzed using descriptive statistics and a learning outcome improvement test (N-Gain). The product feasibility assessment obtained an average score of 3.64 (91%), involving material experts, learning media experts, and Lampung language educators to ensure the quality of the media content and appearance. The effectiveness test showed an increase in learning outcomes with an N-Gain value of 0.67 (medium-high category). Student responses also demonstrated a high level of practicality. The TPACK-based Bubiti e-module proved valid, practical, and effective in improving Lampung literary literacy while also serving as a digital-based cultural preservation medium.